2016
DOI: 10.17511/ijmrr.2016.i02.010
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of conventional methods with gene xpert mtb/rif assay for rapid detection of mycobacterium tuberculosis and rifampicin resistance in extra-pulmonary samples

Abstract: Introduction: Tuberculosis (TB) is a major health problem in India. The World Health Organization has recently in 2010 endorsed the Gene Xpert MTB/RIF assay for rapid detection of smear negative and multidrug resistance tuberculosis and more recently for extra pulmonary tuberculosis. Objectives: Evaluation of role of Cartridge based nucleic acid amplification test (CBNAAT) in extra-pulmonary tuberculosis (EPTB) in comparison with Ziehl Neelsen (ZN) staining and evaluating rifampicin resistance with the same te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 13 publications
1
10
0
Order By: Relevance
“…In a study conducted by Bankar et al GeneXpert MTB/RIF assay displayed 18.42% of positive cases in the detection extrapulmonary tuberculosis as compared to the culture and ZN smear microscopy [39] . In a study performed by Ghariani [40] 77% of cases were positively detected for tuberculosis among the lymph node samples [40] . In Nidhi Gupta et al study out of 143 FNAC samples, GeneXpert Mtuberculosis/RIF assay revealed 60.1% as positive for tuberculous lymphadenitis [41] .…”
Section: Discussionmentioning
confidence: 96%
“…In a study conducted by Bankar et al GeneXpert MTB/RIF assay displayed 18.42% of positive cases in the detection extrapulmonary tuberculosis as compared to the culture and ZN smear microscopy [39] . In a study performed by Ghariani [40] 77% of cases were positively detected for tuberculosis among the lymph node samples [40] . In Nidhi Gupta et al study out of 143 FNAC samples, GeneXpert Mtuberculosis/RIF assay revealed 60.1% as positive for tuberculous lymphadenitis [41] .…”
Section: Discussionmentioning
confidence: 96%
“…Most of the cases of tuberculous lymphadenitis are paucibacillary and Acid-fast bacilli has low sensitivity, as its detection limit is >10 4 bacilli/slide, or 10 4 bacilli per ml (11) and Culture requires a long time of 5-8 weeks to give results, reliance on culture, the gold standard and mainstay of diagnosis often leads to delay, compromising patients care and outcomes. (12) Diagnosis is therefore made on the classical histological changes of chronic granulomatous inflammation suggestive of tuberculosis. (13) Histology remains the most appropriate method till date, but is time-consuming to undertake and establishing a diagnosis of TB with high specificity remains difficult, as it suffers low sensitivity for paucibacillary samples.…”
Section: B a C K G R O U N Dmentioning
confidence: 99%
“…MTB detected (%) Pl fluid LNTB Ascitic fluid Rif resistance (%) Pravin et al [9] 10.1 -9.3 19.2 Avashia S et al [11] 23.3 54.2 20 5.4 Ahmed naeem sajed et al [4] 15.8 -6.3 -Uria GA et al [5] 32 -27.8 -Hillemann D et al [6] 2.9 --4 Shukla et al [15] 20 [5] from India the positivity rate with GeneXpert assay was 24.6% for CSF, 32% for pleural fluid and 27.8% for ascitic fluid. Hillemann et al [6] found 3 positive Gene Xpert results out of 113 pleural fluid samples (2.9%) all of which were negative on mycobacterial culture.…”
Section: Table-1: Comparative Analysis Of Different Studiesmentioning
confidence: 99%
“…Avashia S et al [11] examined 300 various extra-pulmonary samples from suspected extrapulmonary tuberculosis and out of it MTB was detected in 111 samples and 105 samples were rifampicin sensitive and 6 samples were rifampicin resistant (5.40%). Hillman D et al [12] tested 29 strains, all were found to be susceptible to Rifampicin.…”
Section: Table-1: Comparative Analysis Of Different Studiesmentioning
confidence: 99%